WHAT ARE PERSUASIVE LANGUAGES AND STRATEGIES FOR ADVERTORIAL ADVERTISING IN INDONESIA? CRITICAL DISCOURSE ANALYSIS (APA BAHASA DAN STRATEGI PERSUASIF UNTUK PERIKLANAN ADVERTORIAL DI INDONESIA? ANALISIS WACANA KRITIS) - Martutik Martutik; Abdul Rani Abdul Rani; Bambang Prastio; Sainee Thampu; Muhtadin Muhtadin (Jurnal Gramatika, 2023)
To make people aware not to be influenced by discursive practices carried out by capitalists, this study seeks to explore the forms and persuasive strategies of advertorial advertisements found in the newspapers of Jawa Pos, Kompas, and Republika. Through this research, it is expected that people can use the goods and services offered according to their needs, not because they are influenced by persuasive language that is deliberately used by advertising producers. To examine these efforts in discourse can be dismantled through the theory of Critical Discourse Analysis (CDA). This qualitative research shows that persuasive diction in advertorial advertisements uses superlative construction, comparative construction, nominalization, transitive verbs, and adjectives as symbols. In terms of strategy, persuasive diction in advertorials is conveyed by the strategy of providing scholarly images, images of using high technology, images of product effectiveness, images of modern life, prestigious and luxurious images, and images of enjoyment and satisfaction.Advertorials generally have meanings that can represent the experience and knowledge of the community. In short, the findings show that persuasive language aims to build a positive image to potential consumers, through which they can get as much profit as possible. Without realizing what is done by advertising producers through persuasive forms and the strategies they use is a form of hegemony.